2010
DOI: 10.1021/ol102357u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oligoribonucleic Acid Conjugates Using a Cyclooctyne Phosphoramidite

Abstract: The conjugation of a ribonucleic acid 16-mer with the cationic amphiphilic peptide penetratin and an anionic hyaluronan tetrasaccharide by means of Cu-free "click" chemistry is reported. The alkyne-functionalized 16-mer was prepared by automated solid-phase synthesis, using a newly developed strained cyclooctyne phosphoramidite in the final coupling. Cycloaddition of the alkyne functionalized RNA to the azide containing biomolecules led to a clean conversion into the corresponding nucleic acid conjugates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 40 publications
0
39
0
1
Order By: Relevance
“…SPAAC is not a perfect reaction and the formation of regioisomeric triazoles is deemed as an acceptable trade off for the avoidance of a copper catalyst in azide-alkyne bioconjugations. Consistent with triazole formation with little regard for regioselectivity, [32,35] two product peaks were observed for both 16a and 16b; a minimal bias was seen for the regioisomer with slightly longer retention time.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…SPAAC is not a perfect reaction and the formation of regioisomeric triazoles is deemed as an acceptable trade off for the avoidance of a copper catalyst in azide-alkyne bioconjugations. Consistent with triazole formation with little regard for regioselectivity, [32,35] two product peaks were observed for both 16a and 16b; a minimal bias was seen for the regioisomer with slightly longer retention time.…”
Section: Resultsmentioning
confidence: 74%
“…dibenzocyclooctyne. [32,33] It is known that lipid conjugation facilitates both cellular uptake and intracellular delivery of oligonucleotides and so provides hope for a nontoxic alternative to the cationic lipophilic or polymeric siRNA delivery systems, [41,42] and we wished to extend the scope of the SPAAC reaction to include steroidal examples. However, despite the advances in methodologies for the postsynthetic modification of oligonucleotides, the synthesis of steroidal conjugates remains nontrivial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of copper for oligonucleotide conjugation may be compromised due to potential metal-catalyzed strand degradation and/or difficulties in final purification [13][14][15]. Although new ligands reduce the chance of undesired chain cleavage during copper-catalyzed click reaction [16][17][18], strain-promoted azide-alkyne cycloaddition (SPAAC) offers the possibility of oligonucleotide conjugation in the absence of copper [19][20][21][22][23] as demonstrated for oligonucleotides labeled with plain cyclooctyne (OCT) [15] or the more reactive dibenzofused cyclooctyne DIBO [24]. Most recently, Brown et al [25,26] further extended the latter approach by ON incorporation of aminoalkyl thymidine derivatives, followed by selective N-acylation with azide or cyclooctyne after cleavage from support.…”
Section: Introductionmentioning
confidence: 99%
“…The use of azido oligonucleotides gained interest with the introduction of strain-promoted azide−alkyne cycloaddition (SPAAC). 101 The azido compounds can be coupled with both terminal alkynes in a Cu (I)-catalyzed reaction (CuAAC) and strained cycloalkynes. It has been reported that the Staudinger reaction does not take place between the azide group in the support-bound growing nucleotide chain and the phosphoramidite reagents.…”
Section: Scheme 12 Intermolecular H-atom Abstraction By 3'-azt Aminymentioning
confidence: 99%